Association between Sonographic Estimated Fetal Weight and the Risk of Cesarean Delivery among Nulliparous Women with Diabetes in Pregnancy - Dude, Annie M.; Grobman, William A.; Yee, Lynn M. (American Journal of Perinatology, 2018)
Objective The objective of this study was to examine the association between an ultrasound-estimated fetal weight (US-EFW) and mode of delivery among nulliparous diabetic women.Study Design This is a retrospective cohort study of nulliparous women with medication-requiring gestational or pregestational diabetes who delivered term, singleton gestations following a trial of labor. We determined whether having had an US-EFW within 35 days of delivery was associated with cesarean delivery.Results Of 304 women who met the eligibility criteria, 231 (76.0%) had an US-EFW within 35 days of delivery. An US-EFW was associated with increased likelihood of intrapartum cesarean (51.5% for those with an ultrasound vs. 27.4% for those without, p < 0.001); this finding persisted even when controlling for birth weight and other confounding factors (adjusted odds ratio: 2.23, 95% confidence interval: 1.16–4.28). Among women with a recent US-EFW, a diagnosis of a large-for-gestational-age (LGA) fetus was associated with overall intrapartum cesarean frequency (65.2% for women with an LGA fetus vs. 46.1% for those without, p = 0.009), but this association did not remain significant in multivariable models.Conclusion An US-EFW within 35 days of delivery among nulliparous women with medication-requiring diabetes was positively associated with intrapartum cesarean delivery.
Keywords: cesarean delivery; diabetes mellitus; estimated fetal weight; ultrasound